Bank Health Analysis with RGEC Method Panin Dubai Syariah Bank - Faisal Rakhman; Sari Tilawatijariah; Susilawati Susilawati (Research Collaboration Community (RCC), 2023)
Based on the observations, the background of this study is that there are several financial ratios that experience fluctuations and contrary the theory and to find out level of bank health in Panin Dubai Syariah Bank period 2017-2021. This study aims to find out the health level of Panin Dubai Syariah Bank for the period 2017-2021 using the RGEC method. The valuation factors used are Risk Profile, Good Corporate Governance, Earning and Capital factors. The object of this research is the financial statements of research used is quantitative with a descriptive approach. The type of data used in this study is secondary data. The results showed that the health level of Panin Dubai Syariah Bank based on Risk Profile factors gets a healthy predicate, Good Corporate Governance gets a healthy predicate, Earning gets an unhealthy predicate and Capital gets a very healthy predicate.